2009
DOI: 10.1007/s00259-009-1116-y
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT for early prediction of response to neoadjuvant chemotherapy in breast cancer

Abstract: 18F-FDG PET/CT can predict response to neoadjuvant chemotherapy at an early stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 33 publications
3
65
1
1
Order By: Relevance
“…In many studies [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90] that have evaluated a possible role for metabolic evaluation with FDG-PET and PET/ CT, investigators demonstrated a correlation between early changes in FDG uptake, mostly in terms of the SUV max value, after one or two courses of chemotherapy and the final pathologic response upon completion of chemotherapy, or patient outcome (Table 4). A review article including 745 patients in 15 studies indicated that the pooled sensitivity and specificity of FDG-PET for early separation of responders from non-responders could reach 80.5 % (95 % CI, 75.9-84.5 %) and 78.8 % (95 % CI, 74.1-83.0 %), respectively [91].…”
Section: Early Treatment Response Assessmentmentioning
confidence: 99%
“…In many studies [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90] that have evaluated a possible role for metabolic evaluation with FDG-PET and PET/ CT, investigators demonstrated a correlation between early changes in FDG uptake, mostly in terms of the SUV max value, after one or two courses of chemotherapy and the final pathologic response upon completion of chemotherapy, or patient outcome (Table 4). A review article including 745 patients in 15 studies indicated that the pooled sensitivity and specificity of FDG-PET for early separation of responders from non-responders could reach 80.5 % (95 % CI, 75.9-84.5 %) and 78.8 % (95 % CI, 74.1-83.0 %), respectively [91].…”
Section: Early Treatment Response Assessmentmentioning
confidence: 99%
“…In a few papers, determination of tumor blood flow and metabolism with a single injection of FDG was suggested to be an alternative to the less available 15 O-water. Indeed, dynamic FDG-PET can indirectly evaluate blood flow using a two-compartment model [100,102], but it requires an acquisition of 1 hour.…”
Section: Changes In Tumor Blood Flow and Angiogenesismentioning
confidence: 99%
“…Indeed, dynamic FDG-PET can indirectly evaluate blood flow using a two-compartment model [100,102], but it requires an acquisition of 1 hour. Mullani et al [103] used a shorter first-pass method to calculate blood flow by dynamic imaging 2 minutes after FDG injection: it was linearly correlated with the 15 O-water method. Cochet et al [104] demonstrated that, in breast cancer, blood flow determined with this first-pass FDG method was correlated with tumor angiogenesis evaluated by immunohistochemistry.…”
Section: Changes In Tumor Blood Flow and Angiogenesismentioning
confidence: 99%
See 2 more Smart Citations